Mobile phones to support adherence to antiretroviral therapy: what would it cost the Indian National AIDS Control Programme? - Rodrigues, Rashmi (International AIDS Society, 2014)
INTRODUCTION: Adherence to antiretroviral treatment (ART) is critical to maintaining health and good clinical outcomes in people living with HIV/AIDS. To address poor treatment adherence, low-cost interventions using mobile communication technology are being studied. While there are some studies that show an effect of mobile phone reminders on adherence to ART, none has reported on the costs of such reminders for national AIDS programmes. This paper aims to study the costs of mobile phone reminder strategies (mHealth interventions) to support adherence in the context of India's National AIDS Control Program (NACP). METHODS: The study was undertaken at two tertiary level teaching hospitals that implement the NACP in Karnataka state, South India. Costs for a mobile phone reminder application to support adherence, implemented at these sites (i.e. weekly calls, messages or both) were studied. Costs were collected based on the concept of avoidable costs specific to the application. The costs that were assessed were one-time costs and recurrent costs that included fixed and variable costs. A sequential procedure for costing was used. Costs were calculated at national-programme level, individual ART-centre level and individual patient level from the NACP's perspective. The assessed costs were pooled to obtain an annual cost per patient. The type of application, number of ART centres and number of patients on ART were varied in a sensitivity analysis of costs. RESULTS: The Indian NACP would incur a cost of between 79 and 110 INR (USD 1.27–1.77) per patient per year, based on the type of reminder, the number of patients on ART and the number of functioning ART centres. The total programme costs for a scale-up of the mHealth intervention to reach the one million patients expected to be on treatment by 2017 is estimated to be 0.36% of the total five-year national-programme budget. CONCLUSIONS: The cost of the mHealth intervention for ART-adherence support in the context of the Indian NACP is low and is facilitated by the low cost of mobile communication in the country. Extending the use of mobile communication applications beyond adherence support under the national programme could be done relatively inexpensively.